Analysis of the Role of Patient Trust in Improving Health Equity: Case Study at the General Hospital in Aceh Province - Nurmailah Nurmailah; Chrimis Novalinda Ginting; Liena Liena (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Mistrust in healthcare settings presents a substantial obstacle to achieving health equity, particularly in regions with unique socio-cultural contexts. This qualitative study explores the multifaceted role of patient trust in enhancing health equity within general hospitals in the Aceh Province, Indonesia, a region with a complex history and distinct cultural norms. Through a review of recent literature (2020-2025), this analysis focuses on how trust influences patient engagement, healthcare utilization patterns following the implementation of Jaminan Kesehatan Aceh (JKA), and ultimately, health outcomes across the province. The study reveals that while JKA has improved overall healthcare access, geographical disparities and financial constraints beyond insurance coverage continue to hinder equitable healthcare utilization. Furthermore, the crucial role of healthcare providers in building trust through cultural competence, effective communication, and empathy is highlighted. The findings underscore the need for targeted interventions that address the root causes of medical mistrust, promote culturally sensitive care, and reduce the social and economic barriers to accessing quality healthcare. This research emphasizes the critical need for healthcare providers and institutions to actively build and maintain trust, especially with under-represented groups, to ensure equitable access and quality of care and improve health equity in Aceh. Future research should evaluate interventions designed to strengthen patient-provider trust and address social determinants of health.